The Parousia of Christ in the Synoptic Gospels - Owen, Huw Parri (Scottish journal of theology, 1959)
The Second Coming (otherwise called the Parousia)1 of Christ constituted a serious problem for the apostolic Church. One of the earliest of Paul's Epistles (1 Thessalonians) shows how quickly his converts became discouraged when some of their number died before the Lord's appearing. In reply Paul repeats his promise that the Lord will soon return, although in his second epistle he has to give a reminder that Antichrist must first make a final bid for power (1 Thess. 4.15–18, 2 Thess. 2). Similarly the author of Hebrews, writing to a disillusioned and apathetic group of Christians some decades later in the first century, recalls the words of Habakkuk that ‘the Lord will come and not be slow’ (10.37). Finally 2 Peter, the latest book of the New Testament (written, perhaps, as late as the middle of the second century), continues to offer the hope of an imminent Parousia to be accompanied by the world's destruction and renewal (ch. 3). If Christians are tempted to despair they must remember that the word of prophets and Apostles is sure (v. 2) and that with God ‘a thousand years are as one day’ (v. 8).